INCREASING OF THE CORROSION RESISTANCE OF FIBERGLASS PLASTIC REINFORCEMENT THROUGH MODIFICATION OF THE POLYMER BINDER - Bilym, Р.; Firsov, Р.; Nadtochiy, S. (Municipal economy of cities. Series: «Economy science», 2023)
The issue of increasing the corrosion resistance of composite reinforcement, based on glass fiber and epoxy anhydride binder, is considered. The proposed samples of composite reinforcement were manufactured by needle extrusion technology. Glass fibers were evenly distributed in the channels and impregnated with a polymer binder based on epoxy resin. The amount of phenolic modifier in the polymer binder, according to the technological mode of obtaining composite reinforcement, was brought up to 5%. With a further increase in the content of the modifier, the degree of conversion of epoxy groups was no more than 70%, which sharply reduced the operational characteristics of the material. The overall ratio of polymer binder and glass reinforcement in the composite was ~ 60÷40. It was established that at low concentrations of the polymer modifier (up to 5 wt. parts), the processes of ordering and chemical grafting lead to compaction of the molecular grouping in the system, which in our case is characteristic of phenolic resins of the novolach and resol types. At the same time, under the conditions of the production technology, internal stresses in materials of this type increase sharply, which leads to the formation of surface defects (microcracks). At the tip of a crack or defect, sodium ions or other cations under the action of water undergo hydrolysis to form metal hydroxide, which, in turn, causes hydrolysis of siloxane bonds, thus weakening the mesh structure of silicon dioxide. The experimental activation energy was identified with the activation energy of sodium ion diffusion in the glass mass. But the plastic deformation of the glass in the region before the crack is very small, and instead of a uniform distribution of stress, the material cracks along the weakened centers The obtained data indicate that the action of the alkaline environment causes an increased loss of mass of the composite, both for the unmodified and for those modified with traditional phenolic resins. In turn, this ensures a high degree of penetration of alkalis into the volume of the material, access to reinforced fibers with their subsequent damage. To increase the corrosion resistance of composite reinforcement based on an epoxy anhydride binder, it is advisable to use a reactive sulfur-containing phenolic modifier. Its action is based on the ability to maintain the permissible monolithicity of fiberglass in the alkaline environment of concrete, the modulus of elasticity and necessary strength.